Weight Status and Differences in Mobility Performance, Pain Symptoms, and Physical Activity in Older, Knee Osteoarthritis Patients. (25th May 2014) - Garver, Matthew J.; Focht, Brian C.; Dials, Justin; Rose, Mark; Lucas, Alexander R.; Devor, Steven T.; Emery, Charles F.; Hackshaw, Kevin V.; Rejeski, W. Jack
Abstract : Knee osteoarthritis (OA) is a leading cause of functional disability among American adults. Obesity is a strong independent risk factor for OA. While research emphasizes the role of obesity in the OA-physical function relationship, the extent to which weight status impacts salient physical, health, and pain measures in older, knee OA patients is not well delineated. The primary aim of this study was to assess differences in mobility performance (stair climb and 400-meter walk), mobility-related self-efficacy, pain symptoms (WOMAC), and measures of accelerometer-determined physical activity (PA) as a function of weight status. Analysis of covariance was conducted to examine differences on the dependent variables. Obese class III patients were outperformed by their counterparts on nearly every measure of mobility, mobility-related self-efficacy, and the assessment of pain symptoms. These outcomes did not differ among other weight comparisons. Normal weight subjects outperformed classes I, II, and III counterparts on most measures of PA (engagement in moderate or greater PA and total weekly steps). Additionally, overweight participants outperformed obese class II participants and obese class I participants outperformed obese classes II and III participants on total weekly steps. Collectively, these findings underscore the meaningful differences observed in relevant OA outcomes as a function of increasing levels of body weight.